اللاارتياح في وضعية الجلوس لدى مستخدمي الحاسوب - غربي, البشير; محجر, ياسين (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة الى الكشف عن مواطن الاكثر لا ارتياحا في الجسم من وجهة نظر الموظفين بالجامعة والاضرار التي يمكن ان تنجر عن وضعيات الجلوس غير الصحيحة، حيث تمت الدراسة على عينة قوامها 70 موظف وموظفة بجامعة الوادي، تم استخدام المنهج الوصفي الاستكشافي ذلك لملائمته لطبيعة الدراسة، وتم استخدام طريقة بيشوب وكرولات (1970) لمعرفة مدى اللاارتياح في وضعية الجلوس، لتتم تحليل النتائج بوسطة مقاييس النزعة المركزية، و توصلت الدراسة الى أن الموظفين بالجامعة يشعرون بعدم ارتياح في موطن الجسم خلال وضعية الجلوس وهي (منطقة أسفل الظهر، منتصف الظهر، العنق، الكتفين، الردفين) . Abstract: This study aimed to reveal the most uncomfortable places in the body from of the university employees, and the damages that can result from incorrect sitting postures. Where the study was conducted on a sample of 70 male and female employees of the University of El-Oued. The exploratory descriptive method was used suit the nature of the study, The method of Bishop and Crollette (1970) was used to determine the discomfort in the sitting posture. The results are analyzed using measures of central tendency. The study found that university employees feel uncomfortable in the body’s position during the sitting posture (lower back, middle back, neck, shoulders, buttock(
مقال
Keywords: عدم الارتياح؛ وضعية الجلوس؛ موظفي الجامعة؛ وضعيات العمل; discomfort, sitting postures, university employees, working postures